プロセス・ライティングによる指導がライティング・アプリヘンジョンに及ぼす効果 - 杉田, 由仁 (全国英語教育学会紀要, 2003)
The purposes of this research are (1) to investigate the effect of the process writing approach on the writing apprehension of the Japanese university students, and (2) to examine the effect from the gender perspective and from writing achievement. The subjects took "Daly and Miller's Writing Apprehension Test," a questionnaire designed for measuring anxiety in writing English as the pre- and post- tests. Factor analysis was chosen to examine the construct of writing apprehension using the questionnaire and produced the four factors: Enjoyment of Writing, Fear of Evaluation, Negative Perceptions about Writing ability, and Expressing My Opinion. Based on these factors, the reasons why the approach was effective in the reduction of the apprehension were discussed. The investigation results show the following issues: 1) The process writing approach was effective in order to reduce the writing apprehension. 2) The approach was more beneficial to female subjects in a classroom situation than males. 3) High and low achieving writers, and male and female students increased the enjoyment of writing and decreased the writer's negative perception of writing ability. 4) High achieving writers became less apprehensive to express themselves in writing. These results may imply that the process writing approach may lead to a viable solution if writing apprehension is to be reduced.